PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP EFEKTIVITAS PENGENDALIAN PIUTANG DAN KOLEKTABILITAS PIUTANG TAK TERTAGIH PADA BPRS BHAKTI SUMEKAR CABANG PAMEKASAN - Arifuddin Arifuddin; Agus Sugiono (JURNAL AKUNTANSI DAN INVESTASI, 2019)
The purpose of this study is to determine whether the sales accounting information system influences the effectiveness of receivables control and the effectiveness of collectibility of uncollectible receivables in BPRS Bhakti Sumekar, Pamekasan Branch. This type of research uses descriptive quantitative methods. Data collection is done using a questionnaire. From the results of the study it is known that there is a significant relationship between accounting information systems and the effectiveness of accounts receivable control and collectability of uncollectible accounts. The simple correlation coefficient (R) for the effectiveness of receivables control is 0.826, which means that the accounting information system has a close or strong relationship to the effectiveness of accounts receivable control, which is 0.826 or 82.6%. While collectibility of uncollectible accounts of 0.847 means that the input variable consisting of accounting information systems has a close or strong relationship to collectability of uncollectible accounts of 0.847 or 84.7%. The coefficient of determination for the effectiveness of accounts receivable control is obtained value (R2) = 0.683 which means that 68.3% of the effectiveness of the control of accounts receivable can be explained by the accounting information system while the remaining 31.7% is influenced by other variables outside the model studied. uncollectible obtained value (R2) = 0.717 which means that 71.7% collectability of uncollectible accounts can be explained by accounting information systems while the remaining 28.3% is influenced by other variables outside the model studied.